Relationship between subjective well-being and depressive disorders: Novel findings of cohort variations and demographic heterogeneities - Li, Chao; Xia, Yuxin; Zhang, Yuhan (Frontiers in Psychology, 2023)
This paper uses a large-scale nationally representative dataset, Chinese General Social Survey, to examine the relationship between subjective well-being and depressive disorders. Statistical results indicate that higher levels of subjective well-being help decrease depression. Robustness checks are performed using different types of explanatory and dependent variables, various regression models, penalized machine learning methods, instrumental variable approaches and placebo test, all of which lend further credence to above findings. Based on it, heterogeneities in the relationship between subjective well-being and mental disorders are explored. In respect of variations in age cohorts, it is found that the absolute values of happiness’s estimates are smaller in the 20-30 and 30-40 age groups, while that in the 40-50 age group increases substantially. In older cohorts, the estimates remain at higher levels while fluctuating to some degree. Furthermore, the significantly negative interaction between happiness and age proves that age amplifies subjective well-being’s effect on depressive disorders. With age increasing, the impact of happiness on reducing depression tends to be stronger. Therefore, for older people, subjective well-being plays a more important role in suppressing depression. Heterogeneities of the relationship between happiness and depressive disorders in subgroups with different demographic characteristics are also investigated. It is found that the negative correlation between subjective well-being and depression is stronger among those with higher educational levels, living in urban areas, being members of the Communist Party of China, having pensions and owning more housing assets. However, gender, ethnic identity, religious belief and marital status exert no significant moderating effects.